A short introduction to psychiatry - Gask, Linda (Short introductions to the therapy professions., 2004)
A Short Introduction to Psychiatry is designed to give readers a clear picture of the profession as it is today and an understanding of the subject from which to develop further study. Linda Gask describes the development of the profession, the route to qualification and the scope of contemporary practice, including the work done by psychiatrists in a range of specialisms - from child psychiatry to addiction services and forensic psychiatry.